Location and chemical composition of semi-permeable layer of forage seeds - Zhou, Jing; Wang, Yanrong; Jahufer, Zulfi (Bangladesh Journal of Botany, 2013)
The presence of the semi-permeable layer is determined in Roegneria nutans (Keng.) Keng, Achnatherum inebrians (Hance.) Keng, Hordeum vulgare var. nudum Hook. f., Triticale, Festuca sinensis Keng., and Bromus inermis Leyss. using the lanthanum nitrate tracer method, transmission electron microscopy and energy dispersive X-ray analysis. It was an amorphous membranous structure firmly attached on the external portion of the seed coat. The diversified chemical composition of the semi-permeable layer of the species studied is also analyzed by histochemical staining. R. nutans, A. inebrians, H. vulgare var. nudum, and Triticale were found to contain lipids in the semi-permeable layer. F. sinensis had pectin whereas B. inermis has cellulose in the said layer. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15802 Bangladesh J. Bot. 42(1): 23-29, 2013 (June)